Problematika Pembelajaran Matematika pada Siswa Sekolah Menengah: Studi Kualitatif - Putri, Fici Amelia; Herlina, Elda (Papanda, 2026)
Mathematics learning should ideally be conducted in an active, innovative, and student-centered manner to develop students’ critical thinking and problem-solving skills. However, in practice, various problems are still found that hinder the achievement of these objectives. This study aims to analyze the problems of mathematics learning among secondary school students from the perspectives of teachers, students, and the learning environment. The research was conducted at SMAN 1 Pariangan. The research subjects consisted of mathematics teachers and eleventh-grade students. The sampling technique used in this study was purposive sampling, in which respondents were selected based on specific criteria relevant to the research objectives, such as teachers who actively teach mathematics and students who regularly participate in mathematics learning activities. Data were collected through interviews, questionnaires, observations, and documentation to obtain a comprehensive understanding of the problems in mathematics learning from multiple perspectives.This study employed a qualitative approach with a descriptive method. Data were collected through classroom observations, interviews, and analysis of instructional documents, with research subjects consisting of mathematics teachers, students, and school stakeholders. The findings indicate that the problems in mathematics learning are primarily caused by teachers’ limited pedagogical competence, as reflected in the dominance of lecture-based instruction, the suboptimal implementation of innovative learning models, and the minimal use of instructional media. From the student perspective, the findings reveal low learning motivation, limited mathematical ability, and high levels of mathematics anxiety, characterized by fear of making mistakes and low self-confidence. Furthermore, an unconducive learning environment and limited educational facilities, such as the availability of textbooks and instructional media, also hinder the effectiveness of mathematics learning. This study recommends the implementation of innovative learning models, the enhancement of teachers’ pedagogical competence, and the improvement of the learning environment as efforts to improve the quality of mathematics learning in secondary schools.